An Observational Study Of Dengue Induced Hepatic Dysfunction Ina Tertiary Care Hospital Of Gkgh Bhuj (Indian Journal of Applied-Basic Medical Sciences, 2022)
INTRODUCTION: Dengue infection is a major health problem worldwide including our country. Globally the incidence of Dengue has grown dramatically in the recent years. Every year during the monsoon months and later, many parts of the country witness outbreak of dengue infection. 2020 was no exception and we experienced an outbreak of this vector borne disease in Bhuj. An analysis of these patients revealed that in addition to the classical features of fever, body ache, rash and thrombocytopenia and bleeding tendency, there were other features such as liver dysfunction including a preferential rise of SGOT, hepatomegaly, splenomegaly, ascites, gallbladder wall edema and pericholecystic fluid collection.OBJECTIVE: To study clinical, biochemical and radiological changes in the liver of patients with Dengue fever.METHOD: observational and cross-sectional study was conducted on a 50 suspected cases of Dengue fever admitted and diagnosed at GKGH hospital Bhuj in October 2020. Detailed history, clinical examination, biochemical parameters, radiological investigation for liver function was done in all patients. All patients were treated as per NVBDCP guidelines. RESULTS: all patients in our study had hepatic dysfunction in the form of elevated SGOT above normal limits. CONCLUSIONS: Our study shows that there are certain features of Dengue that are not known to be usually associated with it. The presence of raised liver enzymes in all patients (SGOT > SGPT), ascites, hepatomegaly, splenomegaly, and gallbladder edema and pericholecystic fluid collection.
Keywords: Dengue; Hepatic Enzymes; Sgpt; Sgot